Bis{5-methoxy-2- (2-morpholinoethyl)iminomethyl-kappa N phenolato-kappa O-1}nickel(II) - Lair, N.M.; Ng, S.W.; Ali, Hapipah Mohd (International Union of Crystallography, 2009)
The asymmetric unit of the crystal structure of the title compound, [Ni(C14H19N2O3)(2)], contains two independent Ni-II complex molecules, with the metal atoms each located on a center of inversion. Each metal atom is chelated by two Schiff base anions in a distorted square-planar coordination environment.